2021
DOI: 10.1002/qj.3978
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Stochastically Perturbed Parametrisations model uncertainty scheme in the Integrated Forecasting System

Abstract: The Stochastically Perturbed Parametrisations scheme (SPP) represents model uncertainty in numerical weather prediction by introducing stochastic perturbations into the physical parametrisation schemes. The perturbations are constructed in such a way that the internal consistency of the physical parametrisation schemes is preserved. We developed a revised version of SPP for the Integrated Forecasting System of the European Centre for Medium‐Range Weather Forecasts (ECMWF). The revised version introduces pertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…We follow the approach of Lang et al . (2021). CRPS is computed every 24 hr, from 24 hr up to 360 hr for a range of variables.…”
Section: Methods: Model Simulations and Verificationmentioning
confidence: 99%
“…We follow the approach of Lang et al . (2021). CRPS is computed every 24 hr, from 24 hr up to 360 hr for a range of variables.…”
Section: Methods: Model Simulations and Verificationmentioning
confidence: 99%
“…Running large numbers of ensemble forecasts requires substantial computational resources. Leutbecher (2019) demonstrated that the number of ensemble start dates is much more important than the size of the ensemble for extracting the mean probabilistic skill of the system. Thus, we keep the number of start dates high but decrease the ensemble size for the higher resolutions in order to save computational resources: only the T L 159 experiments and the basic set-up for T L 399 were run with the full 50 ensemble members.…”
Section: Experiments Set-upmentioning
confidence: 99%
“…Fair versions of probabilistic skill scores indicate how the system would have scored if it had had an infinite number of ensemble members 1 . Leutbecher (2019) illustrated how a fair version of the continuous ranked probability score (CRPS) can be constructed and also explored how many ensemble members are required to calculate a representative fair CRPS. The recommended ensemble size was set to be four to eight members for scientific testing.…”
Section: Fair Continuous Ranked Probability Score (Crps)mentioning
confidence: 99%
See 2 more Smart Citations